(3eHGOF GdYdGbGJ GdYGeI (B/s - (3GdNWjH, SYGOI QGZHs ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2009)
(3JGQjN GdYdGbGJ GdYGeI, OGFQI GdYdGbGJ GdYGeI GdhXjajI h GdJfXje , eaghe GdYdGbGJ GdYGeI aj GdeDSSGJ h GYOGO GdHMhK , JNWjW GdeTGQjY aj GdYdGbGJ GdYGeI , GdGJUGdGJ , GdGYdGe aj GdYdGbGJ GdYGeI , GdGYdGbGJ GdYGeI aj GdeLGd GdOhdj , GdGYdGbGJ GdYGeI h GdGYdGf , eaghe GdGYdGe h GdYdGbGJ GdYGeI,GdYdGbGJ GdOhdjI h GdOHdheGSjI (B.s
(3eQGLY U(B.240 (3; edGMb U(B.222s
Keywords: (3GdGJUGds; (3GdGYdGes; (3GdYdGbGJ GdYGeIs